Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Young, Black and male : Exploring the intersections of racial and gender identity in an all-Black male high school - Rogers, Leoandra Onnie (New York University, 2012)
From popular culture to academia, there is national panic about the dismal life trajectories of Black males. This "Black male crisis" has contributed to emergent all-Black, all-male schools. Racial identity is commonly used to explain underperformance among Blacks, yet within-group gender disparity signifies the importance of gender relative to race. Minimal research exists on Black males' gender identities, and less on the intersections of gender and race. This longitudinal dissertation used quantitative and qualitative data to examine the development and intersections of racial and gender identity among Black adolescent males transitioning from co-educational grammar schools and entering the ninth grade at an all-Black, all-male high school. Findings are presented in two empirical papers. Paper 1 examined survey data collected from Black males (N = 183) to explain how boys' racial and gender identities were interrelated, changed over time, and influenced their psychological and academic adjustment. Results from the growth curve analysis revealed that boys' racial and gender identities were interrelated with each other and that higher levels of identity attachment were associated with better psychological and academic adjustment. Moreover, the strength of the relationship between gender identity and psychological adjustment increased over time, indicating that gender identity became increasingly important for boys' wellbeing. Paper 2 analyzed interview data with a subsample of Black males (n = 21) to examine how they resisted and accommodated racial and gender stereotypes. Results from the qualitative analysis revealed that boys were aware of the ways that racial and gender stereotypes overlap, but they responded to these stereotypes in different ways. Although some boys accommodated to both racial and gender stereotypes and others resisted these stereotypes, the majority of the boys responded by accommodating to gender stereotypes and resisting racial stereotypes. That is, they tended to perpetuate cultural stereotypes that require males to be the leader, emotionally stoic, and not to be feminine (i.e., gay) while challenging beliefs about the intellectual inferiority and incompetence of Black people. Findings are interpreted within the macro-context of cultural stereotypes and the micro-context of an all-Black male school. Implications for the study of identity, Black males, and single-sex education are discussed.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; adolescence; amériques; approches et analyses; chicago; discipline; genre; hommes* noirs; identité raciale; intersectionnalité; mémoires/thèses; philosophie; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes; étude longitudinale; étude qualitative; étude quantitative

Ethnic, Gender, and Acculturation Influences on Sexual Behaviors - Meston, Cindy M.; Ahrold, Tierney (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
Much research has been conducted on ethnic differences in sexuality, but few studies have systematically assessed the importance of acculturation in sexual behavior. The present study assessed general differences in normative sexual practices in healthy Euro-American, Asian, and Hispanic populations, using measures of acculturation to analyze the relative effects of heritage and mainstream cultures within each group. A total of 1,419 undergraduates (67% Euro-American, 17% Hispanic, 16% Asian; 33% men, 67% women) completed questionnaires which assessed sexual experience and causal sexual behaviors. In concordance with previous studies, Asians reported more conservative levels of sexual experience and frequency of sexual behaviors, fewer lifetime partners, and later ages of sexual debut than Euro-American or Hispanic counterparts. Hispanic reported sexual experiences similar to that of Euro-Americans. There was a significant interaction between mainstream and heritage acculturation in predicting number of lifetime sexual partners in Asian women such that the relationship between heritage acculturation and casual sexual behavior was stronger at lower levels of mainstream acculturation. On the other hand, in Hispanic men, higher levels of mainstream acculturation predicted more casual sexual behavior (one-time sexual encounters and number of lifetime sexual partners) when heritage acculturation was low but less casual sexual behavior when heritage acculturation was high. These results suggest that, for sexual behavior, Hispanic men follow an “ethnogenesis” model of acculturation while Asian women follow an “assimilation” model of acculturation.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexualité; thématiques; états-unis